Assessing collaborative governance of science-policy interface for urban air pollution in Bangkok, Thailand - Kanokchai Mangmesup; Thi, Phuoc Lai Nguyen; Kusakabe, Kyoko; Ekbordin Winijkul; Royal Thai Government Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2024)
Urban air pollution is a critical environmental and health issue in cities worldwide, with adverse effects on both urban populations and ecosystems. The existing literature primarily focuses on the causes and health consequences of air pollution. This study explores the complexities of urban air pollution governance in Bangkok. The research aims to examine how the science-policy interface within collaborative governance framework contributes to the management of urban air pollution in Bangkok. The research investigates three main aspects: stakeholder dynamics and relationships, legal and policy frameworks affecting collaboration, and the effectiveness of current collaborative efforts in addressing air pollution through principled engagement, shared motivation, and joint action capabilities. This research employed a qualitative approach utilizing stakeholder analysis, document analysis, and in-depth interviews. Data were collected from 25 key informants through purposive sampling. The analysis combined assessment of stakeholder influence and interest levels, examination of legal and policy frameworks, and investigation of collaborative processes through data triangulation. The analysis reveals a fragmented institutional landscape in Bangkok's air quality management. While national environmental bodies demonstrate maximum influence and interest, sectoral implementation agencies show only moderate levels of both attributes. Academic institutions maintain notably low influence despite varying levels of interest, highlighting a critical weakness in the science-policy interface. Support and administrative bodies show minimal influence and interest despite their crucial role in resource allocation. This misalignment between authority, interest, and capability significantly impedes effective collaborative governance. The legal framework for air pollution management is predominantly outdated, with penalties that do not reflect current environmental concerns. Laws are scattered across multiple documents and jurisdictions, creating substantial coordination difficulties. The policy planning framework demonstrates strong vertical coherence but weak horizontal coordination. While agencies effectively align with higher-level plans, they operate in parallel with limited integration at the operational level. Planning documents demonstrate a tiered approach to scientific evidence integration across different planning levels. The analysis reveals significant gaps between theoretical frameworks and practical implementation across shared motivation, principled engagement, and capacity for joint action. While shared motivation exists through national agendas and joint KPIs, these mechanisms have not effectively translated into integrated action. Formal interactions primarily serve as platforms for information exchange rather than joint problem solving. The capacity for joint action is constrained by departmentalized budget management and challenges in translating academic knowledge into policy implementation. Bangkok's current approach represents coordination rather than true collaboration, characterized by parallel efforts and limited integration of expertise. The study suggests three key policy implications: the need for comprehensive institutional reform to better align authority with responsibilities, modernization of environmental laws to create a unified regulatory framework, and enhancement of science-policy integration through formal channels for incorporating academic research into policy decisions.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science in Development and Sustainability
Thesis (M. Sc.) - Asian Institute of Technology, 2024
Keywords: Urban pollution -- Thailand -- Bangkok; Air -- Pollution -- Thailand -- Bangkok; Public administration -- Thailand -- Bangkok